Influência de diferentes instrumentos de exploração no comportamento em torção dos instrumentos Mtwo após uso clínico múltiplo - Rodrigo Keigo Lopes Nakagawa (2015)
The mechanical properties, mainly the resistance of endodontic instruments are affected by factors such as diameter, design, chemical composition, physical properties and canal anatomy. Instrument failure can be controlled by creating a manual or mechanical glide path.The aim of this study was to evaluate the torsional resistance of PathFile and Scout RaCe NiTi rotary instruments with the purpose of "glide path after multiple clinical use and the influence of three different preflaring (K-File, PathFile and Scout RaCe) on the torsional resistance of shaping Mtwo files after multiple clinical use. The mechanical behavior wasevaluated by torsion tests, in accordance with specification ISO 3630-1. All instruments showed geometric features within the tolerance limits and no significant difference concerned about the torsional resistance. Despite of one subtle increase in torsional resistance is noted,it is suggested as an effect of simultaneous sterilization methods or by the work hardening of the NiTi alloy. The present study highlights the importance of preparing the glide path before introducing the shaping files and concludes if sterilization does not render rotary NiTi endodontic instruments stronger, it does not result in deleterious effects that could reduce their mechanical resistance.